Enhancing Fish Tolerance To Global Warming Through Swimming Exercise Training: Cardiac plasticity to swimming exercise training in hatchery-reared fish and its implications for thermal tolerance - Pettinau, Luca (fi=Turun yliopisto|en=University of Turku|, 2023)
Anthropogenic climate change is increasing the magnitude and frequency of marine heatwaves, challenging the physiological limits of ectothermic animals, such as fish, and negatively affecting human activities that depend on them, such as aquaculture. Therefore, there is an urgent need to understand the physiological capacity of fish to cope with rising temperatures and provide solutions to increase the resilience of hatchery fish to heatwaves. Previous studies have suggested that thermal tolerance in fish is strongly related to cardiac function. In this thesis, I studied how phenotypic plasticity of cardiac function can help fish to cope with high temperatures. In study I, I investigated whether acclimation to a mild level of hypoxia can induce functional and molecular adjustments similar to those induced by high temperature acclimation, and whether hypoxia acclimation can induce cross-tolerance protection to high temperatures. By measuring the thermal performance curve for maximal heart rate in European sea ass, I have determined that European sea bass do not show evidence of cross-tolerance protection between hypoxia and high temperature. In studies II, III, and IV, I investigated whether improvements in cardiac performance induced by aerobic exercise training could provide cross-tolerance protection to cope with high temperatures in hatchery-reared rainbow trout and brown trout. By training fish with aerobic exercise training, I demonstrated that trained fish have significantly higher cardiac performance and cardiac thermal tolerance, which might help them to face heatwaves. However, the improvement in thermal tolerance was highly dependent on the intensity of the training. Furthermore, in Study IV, the transgenerational effect of maternal exercise training on the thermal tolerance, survival, and growth rate of the offspring were investigated. The results of this study demonstrated that maternal exercise can improve the survival of embryos and growth of offspring without affecting their thermal tolerance and cardiac performance. This thesis provides deeper insights into the cardiac plasticity of fish and its relationship with thermal tolerance. Taken together, these results suggest that exercise training improves cardiac thermal tolerance in hatchery fish and potentially enhances their ability to cope with heatwaves. In the context of global warming, these findings have significant implications for aquaculture sector and conservation programs, providing a valid aquaculture practice to enhance the resilience of fish to climate warming. KEYWORDS: Acclimation, Aquaculture, Brown trout, Cardiac Arrhythmia, Cardiac Plasticity, Climate Change, Conservation Program, European Sea bass, Exercise Training, Hatchery-Reared Fish, Heart Rate, High Temperature, Rainbow trout, Salmonid, Swimming Training, Thermal Tolerance, Training intensity, Transgenerational Plasticity, Water flow

Ilmastonmuutoksen seurauksena merien lämpöaallot voimistuvat ja niiden esiintymistiheys kasvaa. Tämä haastaa vaihtolämpöisten eläinten, kuten kalojen, fysiologiset sietokykyrajat ja voi aiheuttaa ongelmia esimerkiksi vesiviljelylle. Siksi onkin kiireellistä selvittää, miten kalat reagoivat ja pystyvät sopeutumaan kohonneisiin lämpötiloihin. Lisäksi on selvitettävä, voiko kalojen korkeiden lämpötilojen sietoa parantaa kasvatusoloja muuttamalla. Aiemmat tutkimukset ovat osoittaneet, että kalojen lämmönsietokyky liittyy vahvasti sydämen toimintaan. Väitöskirjassani tutkinkin, mikä merkitys sydämen toiminnan fenotyyppisellä plastisuudella on korkeiden lämpötilojen siedossa ja voisiko plastisuutta käyttää hyväksi kalojen kasvatuksessa, kun veden lämpötila nousee. Tutkimuksessa I selvitin, aiheuttaako vähähappisuusaltistus samanlaisia toiminnallisia ja molekyylitason muutoksia kuin altistuminen korkeille lämpötiloille. Päämääränä oli selvittää, voiko altistuminen alhaiseen happipitoisuuteen vaikuttaa korkeiden lämpötilojen sietoon (ristitoleranssi). Meribasseilla tehdyt maksimisykemittaukset kuitenkin viittaavat siihen, että happivajeen ja korkean lämpötilan välillä ei ole ristitoleranssia. Tutkimuksissa II, III ja IV selvitin, miten aerobinen uintiharjoittelu vaikuttaa kalojen sydämen toimintaan ja etenkin voisiko harjoittelu, parantamalla sydämen toimintakykyä, parantaa korkeiden lämpötilojen sietoa. Tutkimukset tehtiin kirjolohilla ja taimenilla. Tutkimuksissa osoitin, että harjoittelu parantaa huomattavasti sydämen toimintakykyä etenkin korkeissa veden lämpötiloissa, mikä saattaa auttaa kaloja selviytymään lämpöaalloista. Lämmönsietokyvyn paraneminen riippui kuitenkin huomattavasti harjoituksen intensiteetistä. Osatyössä IV tutkin myös, miten naaraskalojen harjoittelu vaikuttaa niiden jälkeläisten lämmönsietokykyyn, selviytymiseen ja kasvuun. Tämän tutkimuksen tulokset osoittivat, että naaraiden harjoittelu voi parantaa alkioiden eloonjäämistä ja jälkeläisten kasvua vaikuttamatta kuitenkaan jälkeläisten lämmönsietokykyyn tai sydämen toimintakykyyn. Yhdessä väitöskirjani tulokset viittaavat siihen, että uintiharjoittelu tehostaa kasvatettujen kalojen sydämen toimintaa korkeissa lämpötiloissa ja tätä kautta mahdollisesti auttaa kaloja selviytymään helleaalloista. Näillä tuloksilla on merkittäviä vaikutuksia sekä vesiviljelyyn että kalojen suojeluohjelmiin, sillä ilmastonmuutoksen seurauksena lämpöaallot vääjäämättömästi tulevat lisääntymään. Väitöskirjani tarjoaa uusia mahdollisuuksia ja käytänteitä vesiviljelyyn, mitkä voivat parantaa kalojen sietokykyä ilmaston lämpenemistä vastaan. ASIASANAT: Acclimation, Aquaculture, Brown trout, Cardiac Arrhythmia, Cardiac Plasticity, Climate Change, Conservation Program, European Sea bass, Exercise Training, Hatchery-Reared Fish, Heart Rate, High Temperature, Rainbow trout, Salmonid, Swimming Training, Thermal Tolerance, Training intensity, Transgenerational Plasticity, Water flow.